Pemahaman Penanaman Empat Pilar Kebangsaan terdahap Siswa SMA Negeri 4 Medan (Universitas Medan Area, 2017)
This research is to explain the understanding of four pillars of nationality with students' attitudes facing the development of the growing era. The formulation of the problem of this research is how the relationship of understanding the four pillars of nationality with the attitude of students. The research method used in this research is correlational descriptive method. The sample of research is 44 respondents. Data collection techniques used in this study are interviews and documentation. Based on the results of research that has been done can be seen that there is degree flatness.Â